Spatiotemporal outbreak dynamics of bark and wood-boring insects - Lantschner, Maria Victoria (2023)
Bark and wood-boring insects (BWI) can cause important disturbances in forest ecosystems, and their impact depends on their spatiotemporal dynamics. Populations are usually at stable, low densities but can be disrupted by stochastic perturbations that trigger a transition to an epidemic phase. For less aggressive species, outbreaks die out quickly once the perturbation is removed, while aggressive species exhibit density-dependent feedback mechanisms facilitating persistent landscape-scale outbreaks. The interactions of attributes of tree, stand, landscape- and regional-scale stressors, and insect life history and behavior determine system-specific dynamics. However, most of our knowledge is based on a few species of mainly Holarctic bark beetles. With global change, it is becoming increasingly important to improve our understanding of the frequency and severity of BWI outbreaks.